"Trapped in the reform": Kindergarten teachers' experiences of teacher professionalisation in Buleleng, Indonesia. Issue 1 (January 2018) - Yulindrasari, Hani; Ujianti, Putu Rahayu
Indonesia has been conducting a teacher reform program since 2005. Teachers' low status and the crisis of student achievement are the rationales of this reform. This paper investigates the implications of Indonesian neo-liberal teacher reform on kindergarten teachers' professional experiences and practices. The research was conducted in Buleleng regency, the northern part of Bali Province, Indonesia. This research used focus group discussion to obtain general information about teacher reform/professionalisation in the Buleleng regency. In-depth interviews were conducted to gather richer information about teachers' personal experiences of professionalisation. Drawing from Osgood's deconstruction of professionalism in early childhood education (ECE), this paper argues that the teacher reform policies have failed to recognise the uniqueness of ECE teaching practices, which are centred on emotion and care. The reform has also overlooked the disadvantaged conditions and unequal playing field of kindergarten teachers in the professionalisation process. Thus, despite the improvement of teachers' individual welfare, the "regulatory gaze" of teacher reform policies poses a subtle threat to kindergarten teachers' professional identities.